Prevalence of Delirium in Opium Users after Coronary Artery Bypass Graft Surgery - Eizadi-Mood, Nastaran (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Postoperative cognitive dysfunction, especially delirium commonly occurs after cardiac surgery. Clinical evidences suggest an increase in delirium in opium abusers after Coronary Artery Bypass Graft (CABG) surgery. In this study, the prevalence of delirium in addict (opium user) and nonaddict patients after CABG were compared. METHODS: In a cross-sectional study after obtaining institutional approval and informed consent, 325 patients candidate for elective CABG were included in the study. All patients with history of opium abuse met the criteria for opioid dependence using Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition definitions. Delirium after CABG was assessed in addict (opium user) and nonaddict patients up to a maximum of 5 days after surgery with the Intensive Care Delirium Screening Checklist. RESULTS: A total of 325 patients were evaluated (208 without and 117 with a history of opium abuse). Postoperative delirium occurred within 72 h after surgery in 44.31% of all patients. There was a significant difference in the prevalence of postoperative delirium between the opium users (80.7%) and nonaddict patients (25%) in the intensive care unit (P < 0.001). Opium addiction was a risk factor for postoperative delirium after CABG Surgery. CONCLUSIONS: Delirium after CABG surgery is more prevalent in opium users compared with nonaddict patients. Therefore, opium abuse is a possible risk factor for postoperative delirium in cardiac surgical patients.